COVID-19 vaccination refusal and suspension of work among healthy healthcare personnel in Italy: A cross-sectional study of their knowledge and attitudes toward vaccinations. (April 2023) - Ledda, Caterina; Rapisarda, Venerando; Maltezou, Helena C.
Abstract: Despite the initial optimistic projections from various countries and the evidence that vaccination against coronavirus disease 2019 (COVID-19) reduces the associated hospitalization rates and mortality, vaccine hesitancy and refusal among healthcare personnel (HCP) became a major public health concern globally. The aim of this survey was to estimate the knowledge about the Italian Vaccination Plan for HCP and attitudes about occupational vaccinations for HCP among Italian HCP who refused COVID-19 vaccination and were suspended from work. A total of 52 HCP participated in the study. Nurses were the prevalent profession among vaccination refusers. About COVID-19, 24 (26.2%) of all responders have been involved in COVID-19 care and 21 (40.4%) had a history of COVID-19. None had received influenza and pneumococcus vaccination in the past. Knowledge of vaccinations recommended for HCP was high, ranging from 75% to 98% by vaccine. Instead, all HCP were against any mandatory vaccination policy for all HCP. Finally, most HCP questioned the expected benefits and safety of vaccines in general, raised issues of mistrust of information provided for authorities and of compliance with their HCP' vaccination recommendations. Our study indicates good knowledge of occupational vaccinations but strong anti-vaccination beliefs among Italian HCP who refused COVID-19 vaccination and were suspended from work.